THE DIGITAL MAP OF THE PLIOCENE–QUATERNARY CRUSTAL FAULTS IN THE SOUTHERN EAST SIBERIA AND THE ADJACENT NORTHERN MONGOLIA - O. V. Lunina (Геодинамика и тектонофизика, 2016)
Introduction. Studying and mapping of faults in the Earth’s crust is one of the priority objectives in struc‐ tural geology and tectonophysics. Generally, faults are associated with mineral deposits, thermal springs and earth‐ quakes, and fault zones are areas of the most dangerous geological processes and various geophysical anomalies. In this regard, digital maps and databases on faults and fault zones are highly demanded both for science and practical applications. This paper presents a new digital map of the southern East Siberia and the adjacent Northern Mongolia, which shows faults in the crust which were active in the Pliocene‐Quaternary. The map covers the territory between 96–124°E to 49–58°N. An annex to this paper contains files with geospatial data on the mapped faults.The input data, and their synthesis. We consolidated the database on faults active in the Pliocene‐Quaternary stage of the crust development and mapped the faults on the basis of digital elevation models SRTM 90 m [Consortium for Spatial Information, 2004], space images from Landsat series satellites (Google Earth), electronic bathymetry data on Lake Baikal [Sherstyankin et al., 2006], topographic maps (1:200000 scale), regional and global earthquake cata‐ logs, as well as the publications and maps based on the earlier studies of active tectonics and earthquake traces with the use of the ActiveTectonics Information System developed by the research team lead by the author of this paper [Lunina et al., 2014b]. For the major part of the southern East Siberia, we collected and processed our field observa‐ tion data on faults and related deformation features (Fig. 1). The geographic locations of the faults were mapped with the use of MapInfo GIS. The precise detection of tectonic faults, topographically represented by river lineaments and benching, was ensured by the synthesis of cartographic, literature and field materials. A significant number of the detected lineaments, that were not confirmed by any data due to the poor knowledge of some regions in the southern East Siberia and the adjacent territories, are included in the database with a special mark and shown on the map as inferred faults.Results and discussion. The digital map (Fig. 2) shows 1678 faults composed of 2315 segments, including 1097 true, and 1218 inferred ones, identified by the fault strike changes or fragmentation. Using the consolidated fault da‐ tabase, we constructed maps showing fault segments differing in the degree of activity (Fig. 3), displacement types (Fig. 4 and 7), and ages of the last activations (Fig. 8). Besides, we constructed a map of seismically active faults that can generate M≥5.5 earthquakes. The analysis of the thematic maps of faults gives grounds to conclusions that have been either partly supported or controversial, yet now are based on the factual justification of the faults in the Ac‐ tiveTectonics Information System database. It is shown that the Baikal rift zone is bordered in the southwest by the Busiyngol basin and the West Belino‐Busiyngol fault, and in the northeast by the Olyokma and Nyukzha faults located in the basins of the same‐name rivers. In the areas located westward and eastward of these boundaries, the rift re‐ gime (crustal stretching, extension with strike‐slip faulting, and shearing) is abruptly changed to transpression. In general, similar activation features are typical of the southern East Siberia in the Holocene and the present time. Such features include seismogenic activation episodes when mainly the faults of the NE–SW and sublatitudinal strike are renovated – normal faults, left‐lateral normal faults with a strike‐slip component, left‐lateral strike‐slip faults, left‐ lateral strike‐slip faults with a normal component, and left‐lateral strike‐slip faults with a reverse component. The NE‐ striking faults are insignificant to the west of 98° meridian.Conclusion. The digital fault map (Fig. 2) and the thematic maps (Fig. 3, 4, 7, 8 and 9) can be used as a tectonic ba‐ sis for the synthesis of geological, geophysical, hydrogeological and geodetic data in studies aimed at forecasting of hazardous endogenic and exogenic geological processes. The undoubted advantage of this digital fault map over other regional fault maps is its integrated mapping framework that consolidates a large amount of data (collected mostly by the Siberian scientists) in the uniform information space. Newly gathered data can be input in the map’s database that is available for off‐line viewing on html‐pages.